Selective Biosynthesis of Furoic Acid From Furfural by Pseudomonas Putida and Identification of Molybdate Transporter Involvement in Furfural Oxidation - Zheng, Zhaojuan; Xu, Qianqian; Tan, Huanghong; Zhou, Feng; Ouyang, Jia (Frontiers in Chemistry, 2020)
Upgrading of furanic aldehydes to their corresponding furancarboxylic acids has received considerable interest recently. Herein we reported selective oxidation of furfural (FAL) to furoic acid (FA) with quantitative yield using whole-cells of Pseudomonas putida KT2440. The biocatalytic capacity could be substantially promoted through adding 5-hydroxymethylfurfural into media at the middle exponential growth phase. The reaction pH and cell dosage had notable impacts on both FA titer and selectivity. Based on the validation of key factors for FAL conversion, the capacity of P. putida KT2440 to produce FAL was substantially improved. In batch bioconversion, 170 mM FA was produced with selectivity nearly 100% in 2 h, whereas 204 mM FA was produced with selectivity above 97% in 3 h in fed-batch bioconversion. Particularly, the role of molybdate transporter in oxidation of FAL and 5-hydroxymethylfurfural was demonstrated for the first time. The furancarboxylic acids synthesis was repressed markedly by destroying molybdate transporter, which implied Mo-dependent enzyme/molybdoenzyme played pivotal role in such oxidation reactions. This research further highlights the potential of P. putida KT2440 as next generation industrial workhorse and provides a novel understanding of molybdoenzyme in oxidation of furanic aldehydes.